The 2023 Pazarck (Kahramanmaras, Turkiye) earthquake (Mw 7.7): implications for surface rupture dynamics along the East Anatolian Fault Zone - Karabacak, Volkan; Ozkaymak, Caglar; Sozbilir, Hasan; Tatar, Orhan; Aktug, Bahadir; Ozdag, Ozkan Cevdet; Arslan, Gokhan (Geological Soc Publ House, 2023)
Southern Turkiye faced widespread catastrophic destruction by two devastating earthquakes on the same day. As the earthquakes occurred at 04:17 (M-w = 7.7, Pazarcik, Kahramanmaras) and 12:30 (M-w = 7.6, Elbistan, Kahramanmaras) on 6 February 2023, neighbouring active fault systems were broken in succession between the Hatay and Malatya provinces in the region. The first earthquake, one of the largest earthquakes in this region during the last century, caused major fatalities and widespread damage to infrastructure and buildings, and produced large-scale seismo-gravitational surface deformation such as landslides, lateral spreading, liquefaction and extensional cracks. Here, we present the surface rupture geometry and coseismic displacement characteristics of the fault systems, determined by field observations immediately after the 6 February 2023 Pazarcik (Kahramanmaras, Turkiye) earthquake (M-w = 7.7). Preliminary results show that the total rupture length (L-max) is 270 +/- 10 km on the Karasu, Pazarcik and Erkenek segments of the East Anatolian Fault Zone. Left-lateral strike-slip faulting developed with a maximum horizontal displacement (D-max) of 7.30 m and an average displacement (D-avg) of 3.00 m. Although the surface rupture generally exhibits a narrow deformation zone width of 2-5 m, this expands to 50 m in some sections of the faults. The implications for rupture dynamics suggest that fracture development started on a secondary fault (Narli Fault), transferred to the main fault and triggered the breaking of asperities on the Pazarcik segment, which exhibits a long period of accumulation of stress, to initiate the major rupturing.